Endophytic Diaporthe Associated With Citrus grandis cv. Tomentosa in China - Dong, Zhangyong; Manawasinghe, Ishara S.; Huang, Yinghua; Shu, Yongxin; Phillips, Alan J. L.; Dissanayake, Asha J.; Hyde, Kevin D.; Xiang, Meimei; Luo, Mei (Frontiers in Microbiology, 2021)
Diaporthe species are associated with Citrus as endophytes, pathogens, and saprobes worldwide. However, little is known about Diaporthe as endophytes in Citrus grandis in China. In this study, 24 endophytic Diaporthe isolates were obtained from cultivated C. grandis cv 'Tomentosa' in Huazhou, Guangdong Province, China. The nuclear ribosomal internal transcribed spacer (ITS), partial sequences of translation elongation factor 1-α (TEF1-α), β-tubulin (TUB), and partial calmodulin (CAL) gene regions were sequenced and employed to construct phylogenetic trees. Based on morphology and combined multigene phylogeny, eleven Diaporthe species were identified including two new species, Diaporthe endocitricola and D. guangdongensis. This is the first report of D. apiculata, D. aquatica, D. arecae, D. biconispora, D. limonicola, D. masirevicii, D. passifloricola, D. perseae and D. sennae on C. grandis. This study provides the first intensive study of endophytic Diaporthe species on C. grandis in China. These results will improve the current knowledge of Diaporthe species associated with this traditional medicinal plant. The results obtained in this study will also help to understand the potential pathogens and biocontrol agents and to develop a platform in disease management.